The Realm of Microbial Pigments in the Food Color Market - Rana, Babita; Bhattacharyya, Malini; Patni, Babita; Arya, Mamta; Joshi, Gopal K. (Frontiers in Sustainable Food Systems, 2021)
Colors are added to food items to make them more attractive and appealing. Food colorants therefore, have an impressive market due to the requirements of food industries. A variety of synthetic coloring agents approved as food additives are available and being used in different types of food prepared or manufactured worldwide. However, there is a growing concern that the use of synthetic colors may exert a negative impact on human health and environment in the long run. The natural pigments obtained from animals, plants, and microorganisms are a promising alternative to synthetic food colorants. Compared to animal and plant sources, microorganisms offer many advantages such as no seasonal impact on the quality and quantity of the pigment, ease of handling and genetic manipulation, amenability to large scale production with little or no impact on biodiversity etc. Among the microorganisms algae, fungi and bacteria are being used to produce pigments as food colorants. This review describes the types of microbial food pigments in use, their benefits, production strategies, and associated challenges.